A Guide to Corporate Governance Practices in the European Union - International Finance Corporation (World Bank Group, Washington, DC, 2015)
As one of the most rapidly changing corporate governance environments in the world, Europe represents a microcosm of the exciting innovation happening in the corporate governance arena, ranging from new approaches to board-level corporate governance practices to changes in regulatory requirements at the legislative level. Representing a diverse mix of nations at various stages of economic development and market maturity, the European Union as an entity is demonstrating the broad value of a prioritized focus on corporate governance while accounting for individual country and company circumstances. This publication, a guide to Corporate Governance practices in the European Union, offers an overview of the changes taking place across the EU’s corporate governance landscape. It provides a focused examination of specific regulations and practices as well as a frank assessment of the challenges that remain. The value of this publication is that it examines the issues from all sides. It assesses the steps forward and steps backward, the progress made and the gaps that remain, presenting the sometimes widely varying perspectives of owners, boards, management, and other stakeholders to create a complete picture of the European corporate governance environment.